Use of optical coherence tomography retinal thickness deviation map for hydroxychloroquine retinopathy screening - Jitendra Kumar,; Surabhi Gupta,; Rashmi Kumari, (Asian Journal of Medical Sciences, 2023)
Background: Hydroxychloroquine (HCQS) is widely used to treat several rheumatic and skin diseases and can cause damage to the outer retina, known as HCQS retinopathy, and is common among long-term users of the drug with higher daily dose by weight. The goal of screening for retinopathy is to recognize signs of toxicity at an early enough stage to prevent the loss of visual acuity. Aims and Objectives: This study aimed to evaluate the diagnostic performance of a commercially available retinal thickness deviation map obtained by spectral-domain (SD) optical coherence tomography (OCT) for screening of HCQS retinopathy. Materials and Methods: This study was a prospective comparative study between unaffected (patients who did not develop retina toxicity) and affected (who developed toxicity) of 50 patients of the age group of 14–60 years taking HCQS medication for several dermatological and rheumatologic disorders. The patients who fulfilled the inclusion criteria were screened for HCQS retinal toxicity using SD-OCT, standard automated perimetry, fundus autofluorescence, and comprehensive ophthalmic examinations. Results: In this study, in group 2 patients, 60% were having parafoveal, 30% having perifoveal, and 10% having a mixed pattern (P<0.001) of HCQS retinopathy, and the mean deviation and pattern standard deviation increase as the severity of disease increases (P<0.005). Conclusion: This study concluded that HCQS is a safer drug and can be used safely in these patients with proper HCQS retinal toxicity monitoring with an SD-OCT-generated retinal thickness deviation map and with regular follow-up to monitor reduced thickness in the parafoveal region.